2023
DOI: 10.1371/journal.pone.0286756
|View full text |Cite
|
Sign up to set email alerts
|

MIC26 and MIC27 are bona fide subunits of the MICOS complex in mitochondria and do not exist as glycosylated apolipoproteins

Melissa Lubeck,
Nick H. Derkum,
Ritam Naha
et al.

Abstract: Impairments of mitochondrial functions are linked to human ageing and pathologies such as cancer, cardiomyopathy, neurodegeneration and diabetes. Specifically, aberrations in ultrastructure of mitochondrial inner membrane (IM) and factors regulating them are linked to diabetes. The development of diabetes is connected to the ‘Mitochondrial Contact Site and Cristae Organising System’ (MICOS) complex which is a large membrane protein complex defining the IM architecture. MIC26 and MIC27 are homologous apolipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Cells were grown at 37°C supplied with 5% CO 2 . MIC26 HepG2 KO cells were generated using the double nickase method as described before (Lubeck et al ., 2023). Cells cultured in standard growth media were divided equally into two cell culture flasks and grown in either 1 g/L glucose DMEM (normoglycemia) or 4.5 g/L glucose DMEM (hyperglycemia) (PAN-Biotech) supplemented with above-mentioned reagents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were grown at 37°C supplied with 5% CO 2 . MIC26 HepG2 KO cells were generated using the double nickase method as described before (Lubeck et al ., 2023). Cells cultured in standard growth media were divided equally into two cell culture flasks and grown in either 1 g/L glucose DMEM (normoglycemia) or 4.5 g/L glucose DMEM (hyperglycemia) (PAN-Biotech) supplemented with above-mentioned reagents.…”
Section: Methodsmentioning
confidence: 99%
“…However, the recombinant protein was only observed at the expected size of 22 kDa (Lamant et al ., 2006) and it was later shown that this 22 kDa form is located to mitochondria (Koob et al ., 2015; Ott et al , 2015). Moreover, using several cellular MIC26 deletion models and different antibodies, we showed recently that MIC26 is exclusively present as a 22 kDa mitochondrial protein and not as a 55 kDa protein (Lubeck et al , 2023). In light of these findings, the primary physiological function of MIC26 in diabetes is linked to its role in the mitochondrial IM and not to an earlier proposed secreted form of MIC26.…”
Section: Introductionmentioning
confidence: 99%
“…The 55 KDa band was present even in the KO of MIC26 and mass spectrometry of 55 KDa protein did not contain any MIC26-specific peptides, showing that the 55 KDa band was nonspecific. 39 MIC26 and MIC27 show antagonistic regulation at the protein level where a decrease in the levels of one of them leads to an increase in protein levels of another and vice versa. 38 Although they are not considered as core components of MICOS complex, the double KO of MIC26 and MIC27 shows drastic loss of CJs.…”
Section: Introductionmentioning
confidence: 99%